The Development of VideoScribe Assisted Learning Media to Improve Understanding of Physics Concepts - Jasruddin Jasruddin; Bunga Dara Amin; Silfiani Silfiani (Jurnal Penelitian Pendidikan IPA, 2022)
This research is development research that aims to: describe the feasibility of VideoScribe-assisted learning media, practitioners' assessment of VideoScribe-assisted learning media, the effectiveness of VideoScribe-assisted learning media in physics learning, and produce VideoScribe-assisted learning media. The subjects of this research trial were 20 students in class XI IPA 3 at SMAN 6 Sinjai. This study uses the ADDIE model development. The instruments used in this study were learning media validation sheets, practitioner response questionnaires and students' conceptual understanding test instruments. The eligibility criteria for learning media are seen from the aspect of its validity. The practicality criterion is seen from the practitioner's assessment of the learning media, and the criteria for its effectiveness are seen from the increase in students' concept understanding test results. Based on the results of the analysis, it can be concluded that the VideoScribe assisted learning media developed, based on expert judgment using the Aiken V index analysis, is declared valid and feasible to use with a small revision of the VideoScribe assisted learning media. In terms of the response of physics teacher practitioners, it is in the very good category; and the effectiveness of VideoScribe-assisted learning media seen from students' conceptual understanding abilities analyzed by N-gain obtained an average value of 0.64 in the medium category which means that there is an increase in students' conceptual understanding abilities so that it can be said that VideoScribe-assisted learning media is developed effectively in improving students' conceptual understanding abilities.